Quality Weighted Citations versus Total Citations in the Sciences and Social Sciences, with an Application to Finance and Accounting - Chia-Lin Chang; Michael McAleer (Tinbergen Institute, 2015)
The premise underlying the use of citations data is that higher quality journals generally have a higher number of citations. The impact of citations can be distorted in a number of ways. Journals can, and do, inflate the number of citations through self citation practices, which may be coercive. Another method for distorting journal impact is through a set of journals agreeing to cite each other, that is, by exchanging citations. This may be less coercive than self citations, but is nonetheless unprofessional and distortionary. Both journal self citations and exchanged citations have the effect of increasing a journals impact factor, which may be deceptive. The paper analyses academic journal quality and research impact using quality weighted citations versus total citations, based on the widely-used Thomson Reuters ISI Web of Science citations database (ISI). A new Index of Citations Quality (ICQ) is presented, based on quality weighted citations. The new index is used to analyse the leading 500 journals in both the Sciences and Social Sciences, as well as 58 leading journals in Finance and Accounting, using quantifiable Research Assessment Measures (RAMs) that are based on alternative transformations of citations. It is shown that ICQ is a useful additional measure to 2YIF and other well known RAMs for the purpose of evaluating the impact and quality, as well as ranking, of journals as it contains information that has very low correlations with the information contained in the well known RAMs for both the Sciences and Social Sciences, as well as in Finance and Accounting.
Keywords: C18; C81; Y10; 330; Research assessment measures; Impact factors; Eigenfactor; Article Influence; Quality weighted citations; Total citations; Index of citations quality; Journal rankings; Self citations; Coercive citations; Exchanged citations